Speech intelligibility level determinants and measurement methods - Salheen, Dalal Alfadhil Attaher; Thai, Yap Ngee (Human Resource Management Academic Research Society, 2022)
With the ever-increasing population of non-native speakers (NNSs) of English around the globe to the extent of exceeding the population of native speakers, encountering foreignaccented speech (FAS) has become frequent and inevitable. In this paper, the author highlights English in its new position, and its impact on speech intelligibility. The concept of speech intelligibility is discussed as it correlates with accentedness. It is viewed as an indicator for successful oral communication. A review of the different factors that impact speech intelligibility, in relation to the speakers and others related to the listeners. Moreover, speech intelligibility is modulated in relation to the different factors. Finally, numerous measurement methods that have been used regarding assisting the speech intelligibility of English in general and the intelligibility of English variety are discussed in particular.